Implementasi Pendidikan Profetik Dalam Membentuk Karakter Peserta Didik di Sekolah Dasar Al-Baitul Amien Jember - Pratiwi, Sinta Yulis; Usriyah, Lailatul (EDUCARE: Journal of Primary Education, 2020)
This research was conducted at Al-Baitul Amien Elementary School Jember which aims to answer the problem 1) How is the concept of prophetic education in shaping the character of students in Al-Baitul Amien Elementary School Jember? 2) How is the implementation of prophetic education in shaping the character of students in Al-Baitul Amien Jember Elementary School? 3) How is the evaluation of prophetic education in shaping the character of students at Al-Baitul Amien Elementary School Jember? The method used in this research is qualitative research methods. The approach used is a descriptive qualitative approach. The results of this study indicate: (1) The concept of prophetic education in shaping the character of students at Al-Baitul Amien Elementary School Jember, namely: the formation of a distinctive curriculum based on the historical values ??of the mosque, religious habituation programs, and the commemoration of Islamic holidays. (2) Implementation of prophetic education in shaping the character of students in Al-Baitul Amien Jember Elementary School, namely: Dhuha Prayers, Dhuhr and Asr Prayers in Congregation, Asmaul Husna Habits, Tahfidz Qur'an, Juz 30 Hafalan Program, Tartil Qur'an, Tilawati Qur'an (Qiro'ah), Friday charity, Islamic Studies, Team of action / affection, Learning the Koran, PAI Subjects, Learning Arabic, Student Liaison and Achievement Books, Commemoration of Islamic Holidays, Sholawat and Hadrah, Nasyid, and Da'i Little. (3) Evacuation of prophetic education in shaping the character of students at Al-Baitul Amien Jember Elementary School, namely: a connecting book for reports on the implementation of student sunnah prayers, compulsory prayer services, student morals at home, and also letters from parents to teachers and vice versa. Penelitian ini dilakukan di Sekolah Dasar Al-Baitul Amien Jember yang bertujuan untuk menjawab permasalahan, 1) Bagaimana konsep pendidikan profetik dalam membentuk karakter peserta didik di Sekolah Dasar Al-BaitulAmien Jember? 2) Bagaimana implementasi pendidikan profetik dalam membentuk karakter peserta didik di Sekolah Dasar Al-Baitul Amien Jember? 3) Bagaimana evaluasi pendidikan profetik dalam membentuk karakter peserta didik di Sekolah Dasar Al-Baitul Amien Jember? Pendekatan yang digunakan adalah pendekatan kualitatif deskriptif dan jenis penelitian lapangan (field research). Teknik pengumpulan data menggunakan wawancara, observasi, dan dokumentasi. Dan keabsahan datanya menggunakan triangulasi sumber dan teknik. Hasil penelitian ini menunjukkan: (1) Konsep pendidikan profetik dalam membentuk karakter peserta didik di Sekolah Dasar Al-Baitul Amien Jember yaitu: Kurikulum dibuat berdasarkan nilai historis masjid, program pembiasaan keagamaan, dan peringatan hari besar Islam. (2) Implementasi pendidikan profetik dalam membentuk karakter peserta didik di Sekolah Dasar Al-Baitul Amien Jember yaitu: melalui kegiatan Sholat Dhuha, Sholat Dhuhur dan Ashar berjamaah, Pembiasaan Asmaul Husna, Tahfidz Qur’an, Program Hafalan Juz 30, Tartil Qur’an, Tilawati Qur’an (Qiro’ah), Jum’at beramal, Kajian Islami, Tim penindak/ afeksi, Pembelajaran Al-Qur’an, Mata pelajaran PAI, Pembelajaran Bahasa Arab, Buku Penghubung dan Prestasi Siswa, Peringatan Hari Besar Islam, Sholawat dan Hadrah, Nasyid, dan Da’i Cilik. (3) Evaluasi pendidikan profetik dalam membentuk karakter peserta didik di Sekolah Dasar Al-Baitul Amien Jember yaitu: buku penghubung laporan mengenai pelaksanaan ibadah sholat sunnah siswa, ibadah sholat wajib, akhlak siswa dirumah, dan juga lembar surat dari orang tua kepada guru maupun sebaliknya.